Protective effect of almond oil and primrose oil on neurochemical and lipid profile in ovariectomized rats - Eman Hassan Abdel aziz Sharaf; Enas Ali Kamel; Marwa Mosaad Hassan (Shahrekord University of Medical Sciences, 2023)
Introduction: Ovariectomies rats were used to assess the preventive effects of almond and primrose oils on their lipid and neurochemical profiles. Methods: The experimental groups were as follows: Group 1: A negative control group. Group 2: Rats given an oral dose of almond oil (800 mg/kg/d) for 30 days. Group 3: Rats given an oral dose of primrose oil (500 mg/kg/d) for 30 days. Group 4: Untreated ovariectomized rats. Group 5: Ovariectomized rats given an oral dose of almond oil (800 mg/kg/d) for 30 days. Group 6: Ovariectomized rats given an oral dose (500 mg/kg/d) of primrose oil daily for 30 days. Results: Oral administration of almond and primrose oils significantly decreased mean (P < 0.05) serum total cholesterol (TC), triacylglycerol (TG), low-density lipoprotein cholesterol (LDL-C), and very low-density lipoprotein cholesterol (VLDL-C) concentrations and raised high-density lipoprotein cholesterol (HDL-C) in the ovariectomized groups compared to group 4 (P < 0.05). They also increased leptin and estradiol (E2) concentrations in groups 5 and 6. Administration of oils showed a marked increase in noradrenalin, dopamine, and 5-hydroxytyramin levels and a marked decrease in PGE2 and COX-2 levels (P < 0.05). Rats given almond and primrose oils revealed minor capillary congestion in the hippocampus in brain sections. Conclusion: Administration of almond or primrose oils may improve central nervous system functions and decrease the risk of cardiovascular illnesses. They also might be effective against atherosclerosis, inflammation, endocrine disorders, and cognitive impairments for women who undergo surgical menopause prior to their natural menopause.